Pembekalan Pemrograman Dasar Komputer bagi Guru TIK dan Siswa Terpilih di Tiga Mitra SMA Kabupaten Bangkalan - Sri Wahyuni; Fika Hastarita Rachman; Yonathan Ferry Hendrawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Programming is a basic skill in computing (Teknologi Informasi dan Komunikasi–TIK) feld. In our school partners located at Bangkalan, the teachers of computing course have non-computing background (physics, mathematics, biology). Tis condition means that their programming skill is not good enough. Tis is certainly a suboptimal circumstance since teacher’s mastery of a subject has a lot to do with the success of the teaching-learning process. Computer olympics (olimpiade komputer) is a programming competition for high school students. It has two kinds of tests. Tey were mathematical logic and programming problem solving. Because of the lacking in teacher’s programming skill, the preparation event focused only on mathematical logic. Tis approach had led the students to pass through frst/city selection, but it was not enough to pass the second/provincial selection. In this community service, we gave programming learning modules to the school partners and also train them about pascal programming. Te initial targets were TIK teachers who were also the preparation event coaches. Afer several considerations, we asked the schools to also send their best students as participants for the training. Te purpose were to not only prepare the current participant team, but also to support the regeneration of future teams. By the end of this activity, our partners’ teachers and students have had a better pascal programming skills. Tis result is shown in the increasing scores they get in their pre, mid, and fnal training evaluations.